POLA TATANIAGA SAYURAN DATARAN RENDAH BERBASIS STRUCTURE CONDUCT PERFORMANCE (SCP) - Pujiharto Pujiharto (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2014)
The purpose of this study is to develop a concept of pattern lowland vegetable based trading system structure, conduct, performance (SCP) to function optimally, increasing the income of farmers and sustainable. While the specific targets to be achieved in this study are: 1). to descript pattern trading system lowland vegetables at the study site; 2). to concept of trading system pattern lowland vegetable based structure, conduct, performance (SCP). This research is descriptive-quantitative research. The location chosen purposively research in lowland vegetable production center subdistrict and market. Data were collected through surveys and observation. The unit of analysis is the farmers, traders and trading system actors lowland vegetables. Data analysis was performed by descriptive-quantitative, while the market at the lowland vegetable trading system is analyzed with the approach of structure conduct performance (SCP). The results showed there are four channel pattern trading system lowland vegetables. Lowland vegetable market structure is strongly oligopsonist market structure. Market behavior that occurs as the farm level producers, middlemen, traders, wholesalers and retailers largely indicate a bond provision and capital gains purposes. Farmers obtain the lowest and the highest profit margins are retailers. Value R/C of 1.25 and farmer B/C ratio of 0.25, while the value of R/C ratio of 1.51 the highest on middlemen and B/C wholesaler with the highest value 3.61. Farmer's share of 18.52 %. Elasticity of the price transmission lowland vegetables efficiently due to changes in the consumer price level perfectly transmitted to farmers as producers. Keywords : trading system pattern, lowland vegetables, structure conduct performance (SCP)